Balancing equity and efficiency through health care policies in Slovenia during the period 1990-2008 - Albreht, Tit (Zdravstveno varstvo, 2010)
Background: Slovenia''s 1992 health reform set the following five goals: introduction of social health insurance system and a system of co-payment fora range of health care services; introduction of private practice in healthcare; devolution of planning and control functions from the State to professional associations and municipalitie;, and introduction of licensing and recertification for health professionals. Methods: A descriptive and explorative analysis was done of general demographic, economic and health financing data and the reported data on financing structure. The general population health indicators for the observed period are presented. A broad health policy context was assessed through participatory observation during the whole period and using semi-structured interviews with key national healthpolicy-makers in 2001, which served as a mid-term review. Results: Transformation of health care system in Slovenia led to sustainable health care financing at a level of approx. 8.5% of GDP. This result was achieved atthe expense of reduced public funding, which was partially compensated for by the supplementary health insurance and partially by an increase in out-of-pocket expenditures. Private expenditures increased the system''s regressivity, which was corrected through risk-equalising schemes and by subsidising supplementary health insurance to the least well off. Conclusions: Slovenia''s health care transition took place during a period of economic growth, which afforded stable financing of the system and restricted the capacity of health care providers. This environment had a favourable impact on the general health situation of the population, and thereby reduced pressures on the new system. The previous system was transformed into a mixed social health insurance based system, based on a strong central insurer. The present financing scheme is unlikely to remain sustainable because of demographic trends and other drivers increasing unmet health care needs.
Keywords: financiranje; reforme; Slovenia; Slovenija; zdravstvena politika; zdravstveno varstvo; zdravstveno zavarovanje